Alkali-activated fly ash foam concrete with Yellow River silt: Physico-mechanical and structural properties. (10th April 2023) - Jiang, Sheng; Xu, Jinxia; Song, Yingbin; Xu, Yi
Highlights: Yellow River silt was used as raw materials of alkali-activated foam concrete. The most appropriate dosage of alkali was determined. Yellow River silt dosage was the main factor affecting physical properties. Pore structure was improved by adding Yellow River silt. The main alkali-activation product was hydrated calcium silicate gel. Abstract: Developing innovative techniques to elevate the utilization efficiency of the Yellow River silt (YRS) is very important for the protection of the Yellow River in China. In this study, an approach to use the YRS in the fabrication of alkali-activated fly ash (AAFA) foam concrete was first attempted, and YRS was used as a kind of supplementary binder material. The effects of silt dosage and alkali content on the fluidity, water absorption, compressive strength, drying shrinkage and thermal conductivity of as-fabricated foam concrete with YRS were examined. Besides, the characteristic of pore structure and microstructures of foam concrete were characterized. The results show that the incorporation of YRS significantly affects the physico-mechanical properties of the AAFA foam concrete. With the increase of YRS dosage, the fluidity of fresh foam concrete and the dry density, mechanical properties, thermal conductivity and drying shrinkage of hardened foam concrete is reduced. However, the water absorption and pore structure of foam concrete is improved. In addition, the change of Ca(OH)2 content has a great influence on the physico-mechanical and structural properties of AAFA foam concrete. With the increase of Ca(OH)2 dosage, the dry density and thermal conductivity of AAFA foam concrete is increased obviously. Furthermore, the main hydration product of the AAFA foam concrete with YRS is C-S-H gels. The overall findings demonstrate the feasibility of using YRS as dependable and cost-effective building materials in the preparation of AAFA foam concrete.